2020
DOI: 10.1093/ofid/ofaa486
|View full text |Cite
|
Sign up to set email alerts
|

Antivirals With Adjunctive Corticosteroids Prevent Clinical Progression of Early Coronavirus 2019 Pneumonia: A Retrospective Cohort Study

Abstract: This is a retrospective cohort study of hospitalized adults with COVID-19, 57 received treatment alone and 35 received treatment with adjunctive prednisolone. Combination of corticosteroids and antivirals was associated with lower risk of clinical progression and invasive MV or death in early COVID-19 pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The 631 studies were found after the initial search. After removing duplicates and primarily screening of titles, 34 articles were retrieved, of which 21 articles ( Villar et al, 2020 ; Salton et al, 2020 ; Petersen et al, 2020 ; Horby et al, 2021 ; Steroid SARI, 2020; Tomazini et al, 2020 ; Pontali et al, 2021 ; Rashad et al, 2021 ; Jamaati et al, 2021 ; Edalatifard et al, 2020 ; Ramiro et al, 2020 ; Tang et al, 2021 ; Corral-Gudino et al, 2021 ; Angus et al, 2020 ; Dequin et al, 2020 ; Liu et al, 2020 ; Ranjbar et al, 2021 ; Jeronimo et al, 2021 ; Fadel et al, 2020 ; Nelson et al, 2021 ; Ooi et al, 2020 ) were found to be appropriate for quantitative analysis as presented in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The 631 studies were found after the initial search. After removing duplicates and primarily screening of titles, 34 articles were retrieved, of which 21 articles ( Villar et al, 2020 ; Salton et al, 2020 ; Petersen et al, 2020 ; Horby et al, 2021 ; Steroid SARI, 2020; Tomazini et al, 2020 ; Pontali et al, 2021 ; Rashad et al, 2021 ; Jamaati et al, 2021 ; Edalatifard et al, 2020 ; Ramiro et al, 2020 ; Tang et al, 2021 ; Corral-Gudino et al, 2021 ; Angus et al, 2020 ; Dequin et al, 2020 ; Liu et al, 2020 ; Ranjbar et al, 2021 ; Jeronimo et al, 2021 ; Fadel et al, 2020 ; Nelson et al, 2021 ; Ooi et al, 2020 ) were found to be appropriate for quantitative analysis as presented in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 ] In the study by Ooi et al ., 2020, stage 3 patients requiring supplemental oxygen were considered under severe category. [ 41 ] In the study by Fadel et al's., 2020 included a population which either required supplemental oxygen or mechanical ventilation, so the study population were considered under severe to critical category. [ 42 ] Monreal et al ., 2020 recruited COVID-19 patients who developed ARDS.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Ooi Say Tat et al ., 2020[ 41 ] patients were divided into 3 categories on the basis of severity: stage 1, stage 2, and stage 3. Stage 3 patients requiring supplemental oxygen were considered under severe disease, while stage 1 and 2 not requiring supplemental oxygen were considered under mild to moderate category.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study Dexamethasone with other antiviral drug (remdesivir or favipiravir), it was observed that the use of steroids within ten days of beginning antiviral medications considerably reduces the probability of ICU hospitalization in the early stages of the disease [123] . Corticosteroid was also studied in combination with hydroxychloroquine, an antiviral drug, against hospitalized adults with COVID-19, and result exhibited that the combination of corticosteroid and antiviral drug was related to a reduced risk of clinical development, particularly in patients with pneumonia [124] . Corticosteroids-favipiravir combination treatment was also showed a better result in for improving the condition of COVID-19 patients with chronic obstructive pulmonary disease [125] .…”
Section: Synthesis Of Glucocorticoidsmentioning
confidence: 99%